Analysis of The Influence of Airport Infrastructure, Logistics Costs, and Market Demand on the Development of Aviation Logistics Business in Papua - Lubis, Ukkasyah Sabbit Aqdamana (Dinasti Publisher, 2024)
This study examines the influence of airport infrastructure, logistics costs, and market demand on the development of aviation logistics businesses in Papua, Indonesia. Using an ex-post facto research design with a quantitative approach, data was collected from 57 cargo staff respondents at Sentani Jayapura Airport. Multiple regression analysis reveals that airport infrastructure (? = 0.30, p = 0.004) and market demand (? = 0.35, p = 0.001) have significant positive impacts on aviation logistics business development, while logistics costs (? = -0.25, p = 0.003) have a significant negative effect. The model explains 61% of the variation in business development (R² = 0.61, F (3,53) = 27.80, p < 0.01). The study finds that 45% of respondents believe Papua's airport infrastructure needs substantial improvement, while 55% reported increased demand for logistics services over the past two years. Additionally, 70% of respondents identify transportation costs as the largest expense in their operations. These findings underscore the need for collaborative efforts to enhance infrastructure, manage costs effectively, and adapt to market changes. Recommendations include continued investment in airport facilities, initiatives to reduce logistics costs, and strategies for logistics companies to align their services with evolving market needs.